Kecenderungan Cinderella Complex : Studi Kasus pada Wanita Dewasa Awal yang Sedang Berpacaran di Talawaan Minahasa Utara - Aprilia AR Ismail; Meisie L Mangantes; Marssel M Sengkey (Pusat Riset dan Inovasi Nasional, 2025)
Cinderella Complex is a psychological pattern characterized by emotional dependency of women on men, accompanied by a fear of independence, low self-esteem, a need for external direction, and a tendency to avoid challenges. This condition often develops in individuals who experience the emotional loss of a father figure (fatherless), particularly during adolescence. This study aims to describe the tendency of the Cinderella Complex in early adult women who have experienced fatherlessness and are currently in romantic relationships. The research method employed is qualitative with a case study approach. The subject in this study is a 20-year-old woman from Talawaan, North Minahasa, who meets the criteria of early adulthood, has experienced fatherlessness, and displays characteristics of the Cinderella Complex. Data collection was conducted through in-depth interviews, observation, and documentation, and was validated using source triangulation techniques. The findings indicate that the subject exhibits a strong tendency toward the Cinderella Complex and a high level of dependency in her romantic relationship. The subject demonstrated all aspects of the Cinderella Complex, including dependency on her partner, low self-esteem, external locus of control, and avoidance of decision-making and independence. The study found that the emotional affection resulting from the Cinderella Complex and fatherlessness is unhealthy, manifesting in self-sacrifice, a constant search for validation, and rejection of independence behaviors rooted in emotional wounds caused by the absence of a father figure. These findings are supported by Dowling’s theory of the Cinderella Complex, Bowlby and Ainsworth’s attachment theory, and Maslow’s hierarchy of needs. This study contributes to the field by providing implications for psychological interventions and family counseling.